2020
DOI: 10.1002/joc.6776
|View full text |Cite
|
Sign up to set email alerts
|

Vertical influence of temperature and precipitation on snow cover variability in the Yarlung Zangbo River basin, China

Abstract: Seasonal snow cover in mountainous areas is a key source of water for downstream regions. The snow cover area (SCA) in the Northern Hemisphere has significantly decreased during the past decades in response to global warming. Therefore, it is necessary to investigate the primary factors controlling the spatiotemporal variabilities in the SCA in high altitude regions. In this study, based on remote sensing data of SCA, temperature, and precipitation in the Yarlung Zangbo River basin, Pearson's correlation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Previous studies have shown that the range of glacier change is larger in wetter mountains, such as Eastern Qilian Shan and the Western Tien Shan, while the range of glacier change decreases with the distance from a water vapor supply source. Most studies also showed that temperature played a leading role in hydrothermal conditions, while precipitation played a weaker role (Azam & Srivastava, 2020;Ban et al, 2020;Baojuan et al, 2020;Noel et al, 2020).…”
Section: Impact Factorsmentioning
confidence: 99%
“…Previous studies have shown that the range of glacier change is larger in wetter mountains, such as Eastern Qilian Shan and the Western Tien Shan, while the range of glacier change decreases with the distance from a water vapor supply source. Most studies also showed that temperature played a leading role in hydrothermal conditions, while precipitation played a weaker role (Azam & Srivastava, 2020;Ban et al, 2020;Baojuan et al, 2020;Noel et al, 2020).…”
Section: Impact Factorsmentioning
confidence: 99%
“…The YZR is the highest river in the world with an average elevation of over 4,000 m. The drainage area of the YZR basin (27°40 0 -31°15 0 N, 82°00 0 -97°15 0 E) is approximately 2.4Â10 5 km 2 , and the range of its elevation is 152-7,182 m. The YZR basin has a complex topography and includes several different climate zones from its lower reaches to the upper reaches. The YZR has five major tributaries, i.e., the Duoxiong Zangbo River, Nianchu River, Lhasa River, Nyang River, and Parlung Zangbo River (Ban et al 2020). Average annual precipitation in the upper reaches to the lower reaches varies from 200 to 5,000 mm, respectively (Li et al 2014).…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…of glacier change decreases with the distance from a water vapor supply source. Most studies also showed that temperature played a leading role in hydrothermal conditions, while precipitation played a weaker role (Azam & Srivastava, 2020;Ban et al, 2020;Baojuan et al, 2020;Noel et al, 2020).…”
Section: Impact Factorsmentioning
confidence: 99%